2019
DOI: 10.1002/mrm.27712
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of intracranial arterial blood flow using noncontrast enhanced 4D dynamic MR angiography

Abstract: Purpose: Noncontrast enhanced dynamic magnetic resonance angiography delineates the pattern of dynamic blood flow of the cerebral vasculature. A model-free solution was proposed to quantify arterial blood flow (aBF) by using the monotonic property of the residual function. Theory and Methods: Analytical simulations and in-vivo studies were performed to evaluate the performance of the proposed method by comparing the aBF values generated from the proposed and conventional singular value decomposition methods.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Another emerging application of ASL is non-contrast enhanced time-resolved 4D dynamic magnetic resonance angiography (dMRA) [ 4 – 6 ] that provides the depiction of both the architecture of cerebral vasculature with high spatial resolution (mm) and dynamic flow pattern of labeled blood with high temporal resolution (a few hundred ms). Quantitative hemodynamic parameters are also derived from dMRA, such as arterial blood flow (aBF), arterial blood volume (aBV), ATT, and time-to-peak (TTP) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another emerging application of ASL is non-contrast enhanced time-resolved 4D dynamic magnetic resonance angiography (dMRA) [ 4 – 6 ] that provides the depiction of both the architecture of cerebral vasculature with high spatial resolution (mm) and dynamic flow pattern of labeled blood with high temporal resolution (a few hundred ms). Quantitative hemodynamic parameters are also derived from dMRA, such as arterial blood flow (aBF), arterial blood volume (aBV), ATT, and time-to-peak (TTP) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The voxel‐wise arterial arrival time (AAT) of the intracranial vessels was quantified as the first time point at which the 4D MRA signal was greater than 3× standard deviation of the background noise 34 . Territorial segmentation of cerebroarterial vessels was carried out using an iterative AAT‐based region‐growing algorithm similar to that proposed by Geri et al 5 The implemented algorithm is shown schematically in Figure 1E and is briefly described below:…”
Section: Methodsmentioning
confidence: 99%
“…Although the ideal spatial resolution has not been standardized yet, the voxel-sizes from previous studies are typically 1.0-1.25 mm in in-plane and 1.0-2.0 mm in through-plane direction (potentially reconstructed at even higher resolution). 1,4,[22][23][24] Therefore, the entire scan-time usually needs to be spent for completing k-space, not for signal averaging as in perfusion imaging. The typical readout sequence used for ASL-MRA is based on gradient-echo sequences, such as turbo field-echo (TFE) 2,3 and spoiled gradient-echo (SPGR), [24][25][26][27] in which quite a number of excitation RF-pulses are applied.…”
Section: Spatial Resolution and Readout Sequencementioning
confidence: 99%